THE POLITICIZATION OF ENTERTAINMENT AND ITS IMPACT ON DEMOCRATIC PARTICIPATION: EVIDENCE FROM PILKADA JAWA BARAT - Azarine Charissa Rahma; Fitriyah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study examines the politicization of entertainment and its implications for democratic participation in Indonesia, with a particular focus on the 2024 West Java Local Election (Pilkada Jawa Barat). In the digital era, political communication is no longer confined to traditional media; instead, candidates increasingly rely on entertainment-driven platforms such as TikTok, Instagram, and YouTube, as well as campaign concerts and celebrity endorsements, to engage voters. Drawing on qualitative data from campaign content, media reports, and voter interviews, the findings reveal that entertainment media have become central to political public relations, enabling candidates to build personal brands, cultivate emotional connections, and mobilize younger voters, particularly millennials and Gen Z. The study shows that entertainment media lower barriers to political participation by presenting politics in accessible, culturally familiar, and entertaining formats. However, this trend also carries significant risks, as voter impressions are often shaped more by personality, humor, and popularity than by substantive policy debates. The West Java Pilkada illustrates the hybrid nature of Indonesian democracy, where digital spectacle is combined with traditional cultural and religious campaigning, reflecting both innovation and fragility in political communication. Overall, the research concludes that entertainment media function as a double-edged sword in Indonesian politics: while they democratize access and expand participation, they also risk reinforcing shallow, personality-centered politics that undermine accountability and deliberation. The findings contribute to broader debates on public relations politics, mediatization, and democratic consolidation in the digital era, offering insights for scholars, practitioners, and policymakers concerned with the evolving relationship between media, politics, and democracy.